Podoplanin-positive dilated lymphatic vessels in duodenum associates with three-month mortality in patients with cirrhosis - Juneja, Pinky; Sharma, Aarti; Shasthry, S. M.; Kumar, Guresh; Tripathi, Dinesh M.; Rajan, V.; Rastogi, Archana; Sarin, Shiv K.; Kaur, Savneet (Frontiers in Physiology, 2023)
Abstract Dilated and dysfunctional gut lymphatic vessels (LVs) have been reported in experimental cirrhosis. Here, we studied LVs in duodenal (D2)-biopsies of liver cirrhosis patients and investigated the prognostic role of a LV marker, podoplanin (PDPN), in predicting the mortality of patients with cirrhosis. A prospective, single-center cohort study was performed in liver cirrhosis patients (n=31) and matched healthy controls (n=9). D2-biopsies were obtained during endoscopy procedure, immunostained with PDPN, and scored based on (1) intensity and (2) density of positively-stained LVs per high power field. Gut and systemic inflammation were estimated by quantifying duodenal CD3+ intraepithelial lymphocytes (IELs), CD68+ macrophages, and serum TNF-α and IL-6 levels, respectively. Gut permeability and inflammation as assessed by quantifying gene expression of TJP1, OCLN, TNF-α, and IL-6 in D2-biopsies. Gene expression of LV markers, PDPN (8-fold), and LYVE1 (3-fold) was enhanced in D2-biopsies of cirrhosis patients compared to control (p<0.0001). The mean PDPN score in decompensated cirrhosis patients (6.91+1.26, p<0.0001) was significantly increased as compared to those with compensated (3.25+1.60). PDPN score positively and significantly correlated with the number of IELs (r=0.33), serum TNF-α (r=0.35), and IL-6 (r=0.48) levels, while inversely correlated with TJP1 expression (r=-0.46, p<0.05 each). In Cox regression, the PDPN score was a significant and independent 3-month-mortality predictor in patients (HR: 5.61; 1.08-29.109; p=0.04). The area under the curve for the PDPN score was 84.2, and cutoff value for predicting mortality was ≥6.5 with 100% sensitivity and 75% specificity. Collectively, dilated LVs with high PDPN expression in D2-biopsies is a characteristic feature of patients with decompensated cirrhosis. PDPN score correlates with enhanced gut and systemic inflammation and also associates with 3-month mortality in cirrhosis.